2015
DOI: 10.1186/s13059-014-0570-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long non-coding RNAs highlights tissue-specific expression patterns and epigenetic profiles in normal and psoriatic skin

Abstract: BackgroundAlthough analysis pipelines have been developed to use RNA-seq to identify long non-coding RNAs (lncRNAs), inference of their biological and pathological relevance remains a challenge. As a result, most transcriptome studies of autoimmune disease have only assessed protein-coding transcripts.ResultsWe used RNA-seq data from 99 lesional psoriatic, 27 uninvolved psoriatic, and 90 normal skin biopsies, and applied computational approaches to identify and characterize expressed lncRNAs. We detect 2,942 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
222
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(241 citation statements)
references
References 68 publications
17
222
0
2
Order By: Relevance
“…Most lncRNAs are less conserved than mRNAs and are often expressed at low levels in a cell-type or tissue-specific manner (Tsoi et al, 2015). Therefore, it is difficult to predict whether a given lncRNA is functional or reflects transcriptional noise.…”
Section: Introductionmentioning
confidence: 99%
“…Most lncRNAs are less conserved than mRNAs and are often expressed at low levels in a cell-type or tissue-specific manner (Tsoi et al, 2015). Therefore, it is difficult to predict whether a given lncRNA is functional or reflects transcriptional noise.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-Seq technology has allowed the discovery and analysis of noncoding RNAs, and differential methods have been developed to identify novel lncRNAs in RNA-Seq data [45,46]. Although many studies have highlighted the important roles of lncRNAs indifferent tissues [47,48], little is known about the biological function and significance of lncRNAsduring skeletal muscle development in sheep. High-throughput sequencing was performed using two sheep fetuses at gestational ages of 90 days and 120 days to identify lncRNAs affecting the rapidly increase in muscle fiber number and muscle cross-sectional area during this period.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA were found to have various functions in skin fibroblasts [7,10]. Recent studies disclosed that UV stimulation could alter lncRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [9] found that TSIX, an lncRNA, was overexpressed in systemic sclerosis dermal fibroblasts in vivo and in vitro; the upregulation of TSIX seen in systemic sclerosis fibroblasts might result from activated endogenous TGF-β signaling and play a role in constitutive upregulation of collagen in these cells. Tsoi et al [10] observed that over 40% of the novel lncRNA were differentially expressed, and the proportions of previously annotated lncRNA were lower in psoriasis lesions than uninvolved or normal skin.…”
Section: Introductionmentioning
confidence: 99%